2016
DOI: 10.1158/2159-8290.cd-15-1336
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sequencing, Liquid Biopsies, and Patient-Derived Xenografts for Personalized Medicine in Melanoma

Abstract: Targeted therapies and immunotherapies have transformed melanoma care, extending median survival from ∼9 to over 25 months, but nevertheless most patients still die of their disease. The aim of precision medicine is to tailor care for individual patients and improve outcomes. To this end, we developed protocols to facilitate individualized treatment decisions for patients with advanced melanoma, analyzing 364 samples from 214 patients. Whole exome sequencing (WES) and targeted sequencing of circulating tumor D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(128 citation statements)
references
References 49 publications
4
117
0
2
Order By: Relevance
“…The data utilized in this study were derived from a cutaneous melanoma (20) patient (patient 10) with a BRAF V600E mutation (3). The patient presented with primary melanoma on the back and bilateral axillary nodal metastasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data utilized in this study were derived from a cutaneous melanoma (20) patient (patient 10) with a BRAF V600E mutation (3). The patient presented with primary melanoma on the back and bilateral axillary nodal metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…They provide an excellent tool with which to investigate the dynamics of oncogenesis, tumor heterogeneity, evolution, and responses to therapy (1)(2)(3)(4)(5)(6)(7)(8). This has led to considerable interest in combining them with next-generation sequencing (NGS).…”
Section: Introductionmentioning
confidence: 99%
“…Small trials have shown that circulating tumor DNA level changes can mirror radiologic changes in tumor burden and may predict eventual response to ICI (34,35). These emerging technologies, which require only serial blood sampling and laboratory analysis, may compare favorably with PET/CT in terms of feasibility and accessibility among an increasing population of patients undergoing therapy with ICI.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Girotti et al established a large cohort of 91 melanoma PDTX. Using WES, they integrated the data with ctDNA sequencing and PDTX functional studies to describe a novel strategy for the stratification of naïve patients [61]. Alternatively, PDTX can be used to find protein biomarkers related to drug response.…”
Section: Pdtx In Translational Cancer Research Forestall Treatment Famentioning
confidence: 99%